Defeat in the West - Shulman, Milton; With an Introduction by Jacob, Ian, Sir, Major-General (Rawalpindi Army Education Press, 1949)
Really heavy and detailed account of the Allied armies advance across Europe after Normandy. Lots of details all taken from interviews with German officers conducted by the author immediately after they were captured. Watch out, it's seriously academic and not for the amateur history reader.
Include Bibliography, Notes and Index.
Keywords: World War (1939-1945) -- Military Campaigns -- Western Front World War (1939-1945) -- Germany